2020
DOI: 10.1002/ptr.6792
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive efficacy and safety of a standardized herbal medicinal product of Hibiscus sabdariffa and Olea europaea extracts (NW Roselle): A phase‐II, randomized, double‐blind, captopril‐controlled clinical trial

Abstract: Hypertension is a public health concern that needs immediate attention upon diagnosis. The demand for natural alternatives is on the rise; Hibiscus sabdariffa and Olea europaea are traditionally used for hypertension management in Egypt. In this study, we aimed to investigate the antihypertensive efficacy and safety of two doses of an herbal product of Hibiscus sabdariffa calyxes and Olea europaea leaves (NW Roselle) in Egyptian patients with grade 1 essential hypertension. We equally randomized 134 patients t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 29 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…Notably, the extract powder employed in the trial conducted by Gurrola-Díaz et al exhibited a substantially higher concentration of polyphenols and other constituents compared to the whole powdered form of HS. Another study conducted by Elkafrawy et al found a significant reduction in triglycerides levels at eight weeks with a low dose, fixed combination of Roselle powder and olive leaves' powder taken twice daily (P = 0.038) [19]. However, higher doses of the same combination did not achieve a significant reduction in triglyceride levels, suggesting a dose-dependent effect of combined Roselle powder and olive leaves' powder on triglyceride levels.…”
Section: Metabolic Health Blood Glucose and Lipid Profilementioning
confidence: 94%
See 1 more Smart Citation
“…Notably, the extract powder employed in the trial conducted by Gurrola-Díaz et al exhibited a substantially higher concentration of polyphenols and other constituents compared to the whole powdered form of HS. Another study conducted by Elkafrawy et al found a significant reduction in triglycerides levels at eight weeks with a low dose, fixed combination of Roselle powder and olive leaves' powder taken twice daily (P = 0.038) [19]. However, higher doses of the same combination did not achieve a significant reduction in triglyceride levels, suggesting a dose-dependent effect of combined Roselle powder and olive leaves' powder on triglyceride levels.…”
Section: Metabolic Health Blood Glucose and Lipid Profilementioning
confidence: 94%
“…No clinically significant adverse effects were reported. The observed anti-hypertensive effects were attributed to the phytochemical constituents that mediate ACE inhibition [19].…”
Section: Review Cardiovascular Health and Blood Pressurementioning
confidence: 99%
“…In addition to reducing systemic blood pressure, it decreased left ventricular mass in a dose-dependent manner and increased the surface area and myocardial capillary length density. Elkafrawy N. et al (148) studied the synergistic effects of O. europaea L. and H. sabdariffa L. in Egyptian patients with first-degree hypertension. It was found that this composition, at both high and low doses, was able to reduce mean arterial pressure in a manner comparable with the ACE inhibitor captopril.…”
Section: Berberis Aristata Lmentioning
confidence: 99%
“…Moreover, in a randomized, double-blind clinical trial, a standardized herbal medicinal product containing 1200 mg roselle that was consumed by hypertensive patients for 8 weeks led to a reduction in blood pressure, lowered TG, and reduced mean serum renin and ACE [ 102 ]. A non-randomized quasi-experimental study empirically corroborated that roselle has favorable cardiovascular effects in hypertensive patients, as 4 weeks of roselle ingestion with the dose of 250 mL every day was proven to bring down pulse pressure and heart rate to normal levels, and led to the regression of left ventricular hypertrophy [ 103 ].…”
Section: Clinical Studiesmentioning
confidence: 99%